Probing the role of organic cation transporters in respiratory epithelial cell proliferation in vitro - Shemiss, Ligia (2016)
Introduction: The expression profile of plasma membrane organic cation transporters OCT/Ns has been widely investigated in a variety of cell types including hepatocytes, enterocytes, and renal cells. Their functional characteristics in terms of translocation of a wide range of positively charged compounds have been widely examined as well. Recently, the focus has been on their role in the transportation of inhaled drugs through respiratory epithelial cells. The airway epithelium is considered as a protective barrier against inhaled particulates and infectious agents that may cause damage to epithelial cells resulting in the permeation of harmful agents to the underlying tissue. Therefore, restoration of the lost epithelial cells is essential for maintaining epithelial functions. It has been suggested that OCTs, and particularly OCT1, mediate the release of non-neuronal acetylcholine from the cytosol of airway epithelial cells to the extracellular space where it acts as an auto/paracrine molecule. Furthermore, the OCTN2 gene has been associated with respiratory airway diseases such as asthma. In the current study, we aimed to investigate whether the OCT1 protein plays a role in respiratory wound healing via the transportation of non-neuronal acetylcholine. This has indeed been suggested to play a role in the stimulation of cell proliferation through activation of either muscarinic or nicotinic receptors. Methods: The alveolar epithelial cell line A549 was used as a model of the airway epithelium as it had been reported to express cholinergic components such as acetylcholine, muscarinic and nicotinic receptors. In a first instance, OCT/Ns expression in the cell line was probed at pre and post transcriptional levels using normal polymerase chain reaction (PCR), quantitative PCR (qPCR) and In Cell Western™ ICW, respectively. The intestinal cell line Caco-2 and the broncho-epithelial cell line Calu-3 were used as positive controls. A scratch wound model was then establised to assess the role of OCT/Ns in epithelial repair following injury. Initially, the healing of wounded A549 monolayers was assessed in presence of a panel of OCT/Ns inhibitors using the PrestoBlue™ cell proliferation assay. In the second stage of the study, the OCT1 gene was transiently silenced using short interfering RNAs (siRNAs) and the proliferation of knocked down cells was monitored using the PrestoBlue and Cyquant® cell proliferation assays. Results: Traditional PCR showed that OCT1, OCT3, OCTN1 and OCTN2 were expressed in A549 cells, whereas OCT2 was absent. The levels of the OCT1 and OCTN2 proteins were then relatively quantified in these cells using ICW. Some of the OCT/Ns inhibitors employed exhibited proliferation inhibitory effects on unscratched monolayers, while the bronchodilator ipratropium decreased cell proliferation at high concentration without causing toxic effects. However, it was difficult to determine whether OCT/Ns were likely to be involved in wound repair because the drug exhibits other properties than only an inhibitory effect on these transporters. Following optimisation of the siRNA transfection protocol, the OCT1 gene expression was ultimately decreased to about 60% compared to control cells. Nevertheless, OCT1 knockdown had no effect on cell proliferation post injury as monitored using the PrestoBlue and Cyquant® assays up to 48 hrs post transfection. Conclusions: Decreased levels of the OCT1 protein to about 60% of control did not affect cell proliferation in the A549 cell line. This might be because the protein still exhibited normal functions in terms of translocation of non-neuronal acetylcholine despite a lower expression. A549 cell proliferation may also be governed by molecules present in the cell culture medium such as growth factors rather than by non-neuronal acetylcholine.